Confined placental mosaicism: implications for fetal chromosomal analysis using microarray comparative genomic hybridization. (14th November 2013) - Karampetsou, Evangelia; Morrogh, Deborah; Ballard, Terry; Waters, Jonathan J.; Lench, Nicholas; Chitty, Lyn S.
<x xml:space="preserve">Abstract</x> What's already known about this topic? Use of microarray for prenatal diagnosis increases the detection of pathogenic chromosomal rearrangements. CPM is a well‐established phenomenon occurring in 1–2% of CVS. What does this study add? CPM can occur for submicroscopic copy number changes detected by array CGH in DNA from uncultured CVS. In order to minimise the risk of false‐positive results in these cases, detected copy number changes should be confirmed in a different source of material, such as cultured cells.